The Effectiveness of In-Service Training Program: The Case of Teachers’ Working Culture and Program Development Program Indonesia - Kopsasih, Ade Ahmad; Sujanto, Bedjo; ., Wibowo (International Journal of Scientific Research and Management (IJSRM), 2018)
Professional management of an educational program brings a positive impact on educational outcomes. Therefore, teachers are important pillars in improving learning through professional management of education. The Teacher Work Culture Development Center in Banten Province organizes in-service teacher training as an effort to enhance teacher competences. However, the effectiveness of the in-service training program needs to be systematically studied. This study uses a quantitative approach supported by the qualitative approach. 200 samples were randomly selected from the population consisting of 650participants. Findings indicate that the effectiveness of the in-service training program implemented to enhance teacher competence is quite good, especially in relation to the management of learning. The training process focuses on the pedagogical condition and performance; technical condition and performance; sociological condition and performance; the participants’ activity as well as the psychological and social condition of the learning activity in the training. Focus on the above yields effectiveness. After training, participants are expected to pass on what they acquired during the training to other teachers.